2013
DOI: 10.1177/0148607113499374
|View full text |Cite|
|
Sign up to set email alerts
|

A.S.P.E.N. Clinical Guidelines

Abstract: Background: Due to the high prevalence of obesity in adults, nutrition support clinicians are encountering greater numbers of obese patients who require nutrition support during hospitalization. The purpose of this clinical guideline is to serve as a framework for the nutrition support care of adult patients with obesity. Method: A systematic review of the best available evidence to answer a series of questions regarding management of nutrition support in patients with obesity was undertaken and evaluated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(39 citation statements)
references
References 96 publications
(90 reference statements)
3
30
0
6
Order By: Relevance
“…One hopes to see, in the near future, the publication of physiologically literate RCTs of nutritional regimens that provide early and suitably generous amounts of protein to critically ill proteincatabolic patients, such as 1.5 to 2.0 g protein -equivalent to 1.8 to 2.4 g mixed free amino acids (Hoffer 2011) -per kg of normalized dry body weight per day without calorie overfeeding (Verbruggen et al 2011;Hoffer andBistrian 2012, 2013a;Singer and Cohen 2013;Choban et al 2013;Plank 2013;Singer et al 2014).…”
Section: Need For Better Clinical Research and Practicementioning
confidence: 99%
See 1 more Smart Citation
“…One hopes to see, in the near future, the publication of physiologically literate RCTs of nutritional regimens that provide early and suitably generous amounts of protein to critically ill proteincatabolic patients, such as 1.5 to 2.0 g protein -equivalent to 1.8 to 2.4 g mixed free amino acids (Hoffer 2011) -per kg of normalized dry body weight per day without calorie overfeeding (Verbruggen et al 2011;Hoffer andBistrian 2012, 2013a;Singer and Cohen 2013;Choban et al 2013;Plank 2013;Singer et al 2014).…”
Section: Need For Better Clinical Research and Practicementioning
confidence: 99%
“…Current guidelines recommend providing obese critically ill patients with 2.0-2.5 g protein/kg normalized dry body weight per day while limiting energy provision to 50%-70% of energy expenditure (Choban et al 2013). These wellreasoned recommendations should be rigorously tested, not only in obese patients, but in all protein-catabolic patients whose body fat store is reasonably adequate (Hoffer and Bistrian 2015).…”
Section: Need For Better Clinical Research and Practicementioning
confidence: 99%
“…44 The association between improved mortality and obesity is confounded by malnutrition status, and critically ill obese patients with malnutrition have worse outcomes than do obese patients without malnutrition. 45 However, the commonly used markers for malnutrition, prealbumin and albumin, may not accurately reflect malnutrition.…”
Section: D: Dietmentioning
confidence: 99%
“…However, remarkably, several good-sized (>600 patients) studies on ICU patients have found that obesity was associated with a lower mortality, suggesting that the increased nutrient stores associated with obesity may have survival value. This subject has been well reviewed recently by Choban et al for the American Society of Enteral and Parenteral Nutrition and summarized in Table 16.1 [280]. (6):724 [280] The explanation is clearly complex and needs further investigation before we advocate obesity to protect you should you become critically ill!…”
Section: Principlesmentioning
confidence: 99%
“…This subject has been well reviewed recently by Choban et al for the American Society of Enteral and Parenteral Nutrition and summarized in Table 16.1 [280]. (6):724 [280] The explanation is clearly complex and needs further investigation before we advocate obesity to protect you should you become critically ill!…”
Section: Principlesmentioning
confidence: 99%